2002
DOI: 10.1080/10810730252801183
|View full text |Cite
|
Sign up to set email alerts
|

Youth Performing Arts Entertainment-Education for HIV/AIDS Prevention and Health Promotion: Practice and Research

Abstract: Entertainment-education approaches to health promotion and disease prevention are a popular method for many interventions that target adolescents and young adults. This article documents how this approach is used to educate and influence young people about HIV/AIDS, other sexually transmitted diseases (STDs), and other health issues in the United States. A review of the literature is followed by a two-phase descriptive study of American youth performing arts entertainment-education programs. First, a quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 13 publications
1
63
0
1
Order By: Relevance
“…7 Although these theories were developed specifically with reference to narrative forms of entertainment such as soap operas and serial dramas, these concepts may also apply to song, poetry, comedy, and interpretive dance. EE has been used to inform people of health risks and promote beneficial health behaviors such as HIV testing (Glik et al 2002;Singhal and Rogers 1999).…”
Section: The Media and Entertainment-education Social Marketing Andmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Although these theories were developed specifically with reference to narrative forms of entertainment such as soap operas and serial dramas, these concepts may also apply to song, poetry, comedy, and interpretive dance. EE has been used to inform people of health risks and promote beneficial health behaviors such as HIV testing (Glik et al 2002;Singhal and Rogers 1999).…”
Section: The Media and Entertainment-education Social Marketing Andmentioning
confidence: 99%
“…The arts are widely recognized as an important resource within urban communities. Youth cultural activities oriented around hip hop, traditional dances, and other facets of the visual and performing-arts can play an important role in fostering pro-social norms, cognitive development and in the modeling of and communication of healthy lifestyle choices (Eccles et al 2003;Glik et al 2002;Heath 2001;Hughes and Wilson 2004). Youth involvement in these programs in and of itself may be considered a deterrent to their involvement in risky behaviors.…”
Section: Forming Community Partnershipsmentioning
confidence: 99%
“…Various studies indicate that changes measured after exposure to educational dramas may correspond only partially with program goals. For example, exposure to a play about AIDS caused viewers mainly to show more empathy toward those who got ill (Probart, 1989, as cited in Glik et al, 2002), and the main influence found in a study of the impact of an anti-drug abuse play was an increase in children's knowledge of names of specific illegal drugs, rather than attitude change (Starkey & Orme, 2001). These findings underscore concerns raised by EE researchers regarding possible unintended effects of EE programs (Singhal & Rogers, 2002).…”
mentioning
confidence: 99%
“…In various countries professionally produced "live" dramas are considered a popular and effective EE approach to address sensitive issues such as AIDS, alcohol or drug abuse, sexual assault, eating disorders, and violence (e.g., Valente & Bharath, 1999). Because relatively few studies have been published that examined the impact of such dramas, particularly in the context of industrialized countries (Glik, Nowak, Valente, Sapsis, Martin, 2002), it is important to invesCorrespondence should be addressed to Nurit Guttman, Department of Communication, Faculty of Social Sciences, Tel Aviv University, Tel Aviv 69978, Israel. E-mail: guttman@post.tau.ac.il tigate whether they are based on EE theory and produce the intended impact (Greenberg, Salmon, Patel, Beck, & Cole, 2004;Salmon & Murray-Johnson, 2001).…”
mentioning
confidence: 99%
“…Rolspel en direkte interaksie met die gemeenskap maak dit 'n goeie deelnemende metode waar massakommunikasie en interpersoonlike kommunikasie met mekaar versoen word (vgl. Glik et al, 2002;Panford et al, 2001;Gallavotti et al, 2001). Watter metodes ook al gebruik word -die metode moet help om die gemeenskap betrokke te maak en volhoubare vennootskappe te bou en te behou.…”
Section: Implikasies Op Gemeenskapsvlakunclassified